A novel survey for young substellar objects with the W-band filter IV: detection and characterization of low-mass brown dwarfs in Serpens Core. Issue 3 (9th February 2023) - Dubber, Sophie; Biller, Beth; Albert, Loïc; Liu, Michael; Jose, Jessy; Zhang, Zhoujian; Chen, Wen-Ping; Lalchand, Bhavana; Damian, Belinda; Sharma, Tanvi; Allers, Katelyn
ABSTRACT: We present spectroscopic confirmation of nine M5 or later Serpens Core candidate members, identified using a combination of CFHT WIRCam photometry and IRTF SpeX spectroscopy. Through spectral fitting, we find that the latest of these nine candidate members is best fit by an L0 spectral standard (in the range of M8–L2), implying a mass of ∼0.01–0.035M⊙ . If confirmed as a cluster member, this would be one of the lowest mass Serpens Core objects ever discovered. We present analysis of the physical properties of the sample, as well as the likely membership of the candidate Serpens Core members.